PERSEPSI MAHASISWA TERHADAPFUNGSI PARTAI POLITIK SEBAGAI SOSIALISASI POLITIK - ATLANTA (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2017)
The function of political parties as political socialization is the cornerstone of a progressive democracy as a liaison between the aspirations of the people and the government, where in the functioning of socialization of political parties there are many issues such as political mobilization, money politics and lawlessness by political actors such as corruption and bribery. So that political parties should further strengthen its function as political socialization so as not to misuse for the sake of the progress and welfare of society, and maintain a good political image in the social life of society. This study aims to describe the students' perceptions of the running of the function of the socialization of political parties according to law no. 2 Year 2011. That is to form a patterned attitude and political behavior patterned and systemic so that formed a political culture that supports the basic principles of democratic system. So that descriptive qualitative research that is describe and explain in detail the subject under study in the field by observation and interview. Based on the results of this study the perception of students on the function of political parties as political socialization Palangka Raya City still not balanced Although the delivery of political socialization can still be absorbed and accepted by the community but there are many misuse of the function of political parties as political socialization such as money politics, political promises not fulfilled by political actors because of the individual interests of political actors in a priority, so that the political image according to Perceptions of students that occur in society that the political image is bad, because the function of political parties as political socialization has not been able to answer and realize the aspirations of society and political promises. The future expectation of Political Parties is able to meet the demands of the people's aspirations and promises not just a promise as a ladder for power, so that with the fulfillment of the demands of people's aspirations and campaign promises are fulfilled then the interests between political parties and the community will be balanced.   Kata kunci: persepsi, partai, politik, mahasiswa